2020
DOI: 10.1177/1749602019892463
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Soap Operas: A case study on the emergence of an original production culture

Abstract: In a context of ever greater circulation of televisual content of all genres and formats, this article focuses on the intersections between the global and the local to understand how a specific genre – soap opera – was localised in a specific cultural and geographical setting giving origin to a specific local production model. Our general argument draws on the empirical findings of original research on the moulding of the televisual genre called ‘telenovela’ in Portugal, the specific production mode associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In this context, Portugal is an interesting case study. Unlike other European countries, the ownership of production companies by international conglomerates in Portugal is not the norm, as our previous research showed (Damásio & Costa, 2020). This does not mean that the global players and flows do not shape national cinema and audiovisual production.…”
Section: Towards a Creative Economy Of Film And Audiovisual Sectors: ...mentioning
confidence: 66%
See 3 more Smart Citations
“…In this context, Portugal is an interesting case study. Unlike other European countries, the ownership of production companies by international conglomerates in Portugal is not the norm, as our previous research showed (Damásio & Costa, 2020). This does not mean that the global players and flows do not shape national cinema and audiovisual production.…”
Section: Towards a Creative Economy Of Film And Audiovisual Sectors: ...mentioning
confidence: 66%
“…In dialogue with the field of production studies in film and AV (M. J. Banks et al, 2016;Caldwell, 2008), and based on our previous work on television production (Damásio & Costa, 2020), our proposal includes the analysis of the different individual and collective actors (workers and companies) that mold the structure of the film and AV industry. This dimension enables us to capture how the industry workplace's practices and ideologies, and the working conditions of creative workers affect the film value chain itself.…”
Section: Conceptualising the Film And Audiovisual Sectors Within The ...mentioning
confidence: 99%
See 2 more Smart Citations